Histopathological Analysis of Quails in the Trans-Pecos Ecoregion of Texas - Trey E. Johnson; Carlos E. Gonzalez; Dale Rollins; Josh G. Cross; Ryan S. Luna (National Quail Symposium Proceedings, 2022)
Quail populations in Texas, USA, have declined over the past few decades due primarily to habitat loss. The role that parasites may play in such declines has been a recent topic of concern. To help address this question, we collected 12 scaled quail (Callipepla squamata), 8 Gambel’s quail (Callipepla gambelii), and 3 Montezuma quail (Cyrtonyx montezumae) from across the Trans-Pecos ecoregion of Texas via hunter harvest, funnel traps, and night netting. Quail samples were necropsied to determine the abundance of eyeworms (Oxyspirura petrowi). Histopathological analyses were conducted on quail eyeballs and periocular tissues to gain information on parasite-related tissue damage and document other pathogenic factors. We calculated mean abundances of Oxyspirura petrowi for sampled scaled (x̄ = 5.5, standard deviation [SD] = 2.5, x̃ = 3, n = 12), Gambel’s (x̄ = 6.4, SD = 4.2, x̃ = 1.5, n = 8), and Montezuma quail (x̄ = 13, SD = 1.5, x̃ = 13, n = 3). Host tissues exhibited immune responses (i.e., lymphocytic conjunctivitis and plasmacytic adenitis) to O. petrowi. The observed immune responses indicated relatively mild irritation within the ocular tissues. It has been speculated that such irritation to ocular tissues could negatively impact quail vision. This potential impact is worth noting because quails rely on keen vision to detect predators. Future research should focus on measuring the effects of O. petrowi infections on quail survival.
Keywords: Callipepla gambelii; Callipepla squamata; Cyrtonyx montezumae; Histopathology; Oxyspirura petrowi; parasite; Texas